Visual Sociology: The Sociological Analysis of the Image - Abdelghani, Hosni Ibrahim; Almamari, Wafa Said; Saleh, Emad Farouk; Abdrabou, Magdy Mostafa (Journal of Ecohumanism, 2025)
Visual sociology, as defined by the International Visual Sociology Association, is a branch of sociology that examines social phenomena through visual materials such as photographs, films, and other images. It employs visual research methods to gain insights into social issues, identities, and relationships, emphasizing the role of visual materials in conveying social meanings and power dynamics. This article explores this vital field of sociology by tracing its origins and historical development, highlighting key research topics, and discussing some of its main issues. Additionally, it examines the state of this discipline within Arab and Islamic cultures. A content analysis Method was adopted to deconstruct the social and cultural issues associated with images and to underscore the importance of sociological analysis in understanding visual phenomena. Additionally, the historical method was used to trace the emergence and development of visual sociology.